The Utilization of Chatbots in Education to Augment Critical Thinking and Problem-Solving Abilities - Ellina Rienovita; Budi Setiawan; Efrilla Niza (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2025)
Learning in the digital era opens up various new opportunities to enhance the quality of education, particularly in the teaching and learning process through technology integration. One such technology is artificial intelligence (AI), an innovation that can support the learning process. One application of AI is the chatbot—a conversation-based application now widely used across different fields. This study aims to understand how the use of a learning chatbot in vocational videography subjects within the Visual Communication Design (DKV) major can enhance students' critical thinking and problem-solving skills. This study was conducted because, in practice, these two skills still need further improvement, especially in complex subjects like vocational lesson content within the DKV major, which includes videography. In this study, the chatbot functions as an application that provides interactive support and presents content through conversations, exercise guidance, and simulations relevant to real-world videography scenarios. The chatbot is designed to help students grasp fundamental concepts, offer a discussion space, and provide immediate responses at each stage of learning. The research used a quasi-experimental method with two groups: an experimental group using the chatbot and a control group using interactive media. The results showed a significant improvement in the experimental group, with higher scores than the control group that used interactive media. These findings conclude that chatbots are effective in enhancing students' critical thinking and problem-solving skills and have potential for application in other educational areas.